Do Phoenix Miracles Exist? Firm-Level Evidence from Financial Crises - Ayyagari, Meghana; Demirgüç-Kunt, Asli; Maksimovic, Vojislav (2012)
This paper provides empirical evidence on firm recoveries from financial system collapses in developing countries (systemic sudden stops episodes), and compares them with the experience in the United States in the 2008 financial crisis. Prior research found that economies recover from systemic sudden stop episodes before the financial sector. These recoveries are called Phoenix miracles, and the research questioned the role of the financial system in recovery. Although an average of the macro data across a sample of systemic sudden stop episodes over the 1990s appears consistent with the notion of Phoenix recoveries, closer inspection reveals heterogeneity of responses across the countries, with only a few countries fitting the pattern. Micro data show that across countries, only a small fraction (less than 31 percent) of firms follow a pattern of recovery in sales without a recovery in external credit, and even these firms have access to external sources of cash. The experience of firms in the United States during the 2008 financial crisis also suggests no evidence of credit-less recoveries. An examination of the dynamics of firms' financing, investment and payout policies during recovery periods shows that far from being constrained, the firms in the sample are able to access long-term financing, issue equity, and significantly expand their cash holdings.